Pengembangan Instrumen Penilaian Pemahaman Konsep Matematika Siswa SD Negeri Kembangbahu 1 Pada Materi Perkalian - Della Fatwa Kus Anggraini; Arissona Dia Indah Sari (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study was to determine the feasibility of a multiplication material mathematics assessment instrument developed for fourth grade students at SD Negeri Kembangbahu 1. This study used the ADDIE development research methodology and used quantitative techniques as data analysis. The questionnaires used were validation questionnaires, student response questionnaires, and test questions. Data is collected from the results of the questionnaire used. The results of this study indicate that the assessment instrument developed to assess conceptual understanding is feasible and valid. Evidenced by the average results of the validation of the two validators obtaining 98.6% in the valid category, the results of the students' concept understanding test obtained an average percentage above 70%, which is equal to 83,3%, and the results of positive responses students received an average percentage of 88,7% with very good criteria.